Buddhist Attitude towards Health Related Physical Fitness in Kathmandu Valley - Shrestha, Madhav Kumar (Tribhuvan University Journal, 2020)
This study entitled “Buddhist Attitude towards Health Related Physical Fitness in Kathmandu Valley”, was carried out to find out the Buddhist attitude towards health related physical fitness. The necessary information was taken from six Monasteries and Bihars of Kathmandu Valley. Altogether, there were 310 respondents for quantitative data and six respondents for qualitative data. The major source of data was primary. The researcher used attitude scale and in-depth interview for data collection. The researcher found that the health-related physical fitness is most important aspect for improving physical condition, fighting against diseases, to reduce stress and maintaining mental fitness. Similarly, it helps us to maintain the degree of health, bodily posture, physique, proper functioning of organs and good health habits along with an adequate amount of endurance, strength, stamina and flexibility. Another finding highlighted that, through meditation and walking meditation, the body achieves a greater state of balance and breathing is regulated. Our mind becomes focused, clear, and organized. Unnecessary desires and improper thoughts are eliminated.  Most of the Buddhist have had positive attitude towards health related physical fitness.